2004
DOI: 10.3354/dao058017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cryptobia salmositica-induced anorexia on feeding behavior and immune response in juvenile rainbow trout Oncorhynchus mykiss

Abstract: At 10°C, rainbow trout Oncorhynchus mykiss (n = 13 per group) infected with Cryptobia salmositica Katz, 1951 became anorexic at 3 wk post-infection (w.p.i.), with feed-intake decreasing significantly from 1.33 to 0.94% body weight (b.w.). Anorexia was most severe at 4 w.p.i. (0.80% b.w.), coinciding with peak parasitemia (9.2 × 10 6 parasites ml blood -1) and anemia. At 8 w.p.i., fish had recovered their appetite although they still had contained detectable parasites (6.8 × 10 5 parasites ml ) and low PCV (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
6
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
(60 reference statements)
5
6
0
Order By: Relevance
“…Together, these results suggest that the expression of hepatic leptin in rainbow trout is stimulated by hypoxemic conditions and that the appetite-suppressing effects of C. salmositica infection are at least partly mediated by leptin. The parasitemia and hematocrit changes observed in this study are consistent with the known progression of C. salmositica infection in salmonids (Woo & Wehnert 1986, Beamish et al 1996, Chin et al 2004. The number of blood parasites peaked during acute infection at 3-4 wpi and subsequently declined in correspondence with a large increase in the production of Cryptobia-agglutinating antibodies (Sitja-Bobadilla & Woo 1994, Chin et al 2004.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Together, these results suggest that the expression of hepatic leptin in rainbow trout is stimulated by hypoxemic conditions and that the appetite-suppressing effects of C. salmositica infection are at least partly mediated by leptin. The parasitemia and hematocrit changes observed in this study are consistent with the known progression of C. salmositica infection in salmonids (Woo & Wehnert 1986, Beamish et al 1996, Chin et al 2004. The number of blood parasites peaked during acute infection at 3-4 wpi and subsequently declined in correspondence with a large increase in the production of Cryptobia-agglutinating antibodies (Sitja-Bobadilla & Woo 1994, Chin et al 2004.…”
Section: Discussionsupporting
confidence: 74%
“…Among the different parasites known to affect feeding in fish, the effects of the pathogenic hemoflagellate, Cryptobia salmositica (order Parabodonida, class Kinetoplastea), on food intake in rainbow trout have been well characterized (Woo 2003). While the onset of anorexia in Cryptobia-infected fish coincides with a significant rise in parasitemia and a decrease in hematocrit, the return of appetite is associated with the establishment of an immune response that significantly reduces both the parasitemia and anemia (Li & Woo 1991, Thomas & Woo 1992, Chin et al 2004. During acute infection, Cryptobia-infected fish are also characterized by a reduced aerobic scope (Kumaraguru et al 1995) and an increased susceptibility to hypoxia (Woo & Wehnert 1986).…”
Section: Introductionmentioning
confidence: 99%
“…This study also confirms earlier reports (e.g. Li & Woo 1995, Aredelli & Woo 2002, Chin et al 2004) that the humoral response to the vaccine is an important component in protection against cryptobiosis. …”
Section: Discussionsupporting
confidence: 92%
“…Clinical signs of cryptobiosis include exophthalmia, splenomegaly, abdominal distension, ascites fluid, anaemia (Woo 1979), and anorexia (Thomas & Woo 1992, Chin et al 2004. The pathogen has been found in all species of Pacific Oncorhynchus occurring along the west coast of North America, and it is transmitted in streams and rivers by the freshwater leech Piscicola salmositica (Woo 2003).…”
Section: Introductionmentioning
confidence: 99%
“…w4 wpi) is associated with marked decreases in head kidney and spleen il1b mRNA expression (L E MacDonald, S L Alderman, S Kramer, P T K Woo & N J Bernier 2013 unpublished observations). Alternatively, the hypoxaemic conditions triggered by the w50% reduction in haematocrit in C. salmositica-infected rainbow trout (Chin et al 2004) may be responsible for the increase in POA crf gene expression. Previously, we have shown that hypoxia exposure can increase the gene expression of POA crf in rainbow trout .…”
Section: Discussionmentioning
confidence: 99%